Riau Malay Identity Politics - Muhammad Rafi; Eko Priyo Purnomo; Baskoro Wicaksono (Universitas Andalas, 2020)
This article is a study of the process of the rise of Riau Malay Identity Politics when it was previously marginalized in the New Order era. The purpose of this article is to look at the stages in the formation of identity politics in restoring the glory of Malay culture in Riau province. This research is descriptive-explorative library research that explains and explores ideas about Riau Malay identity politics by answering questions in problems identified based on reading results and data interpretation related to the research theme. The results showed that after the reforms, the political elite of the Riau Province government tried to strengthen Malay identity with a variety of policies that were disseminated. Then, the negative views that were often directed towards ethnic Malay in the past, were rectified again by giving Islamic values to all the lives of the Malay people. Furthermore, the Local Government and the Riau Malay Customary Institution try to re-socialize the importance of the use of Malay as the origin of Indonesian.